2020
DOI: 10.22159/ajpcr.2020.v13i10.38698
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of Five Plant Extracts Against Different Human Cancer Cell Lines and Their Molecular Mechanism

Abstract: Objective: Five methanol plant extracts namely, Euphorbia hierosolymitana, Dracaena marginata, Cordyline terminalis, and Sapium sebifera were screened in vitro for their cytotoxic effect on human tumor cell lines; namely, PC-3, HepG-2, HCT-116, and MCF-7 (prostate, liver, colon, and breast cancer) and human normal cell lines, namely, BJ-1. Methods: E. hierosolymitana (extract A) selectively inhibited HCT-116 cell proliferation with IC50 of 4.22 μg/ml, both Dracaena marginata (extract B) (bark, leaves, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Cytotoxicity of euphodendrophanes A, B, C, D, E F, and tigliane euphodendriane A isolated from Euphorbia dendroides on DLD-1 line was reported with IC50 values of 59.3, 22.1, 42.7, 37.9, 75.3, and 27.4 µM, respectively (Aljancic et al, 2011). Superior cytotoxic effect was observed in the methanol extract of Euphorbia hierosolymitana on HCT-116 cell line with IC50 value of 4.22 µg/mL (El-Hallouty et al, 2020). Mesas et al (2021) reported the cytotoxic effect of Euphorbia lathyris ethanol extract (IC50: 72.9±1.27 µg/mL) against HCT-115 cell line.…”
Section: Discussionmentioning
confidence: 97%
“…Cytotoxicity of euphodendrophanes A, B, C, D, E F, and tigliane euphodendriane A isolated from Euphorbia dendroides on DLD-1 line was reported with IC50 values of 59.3, 22.1, 42.7, 37.9, 75.3, and 27.4 µM, respectively (Aljancic et al, 2011). Superior cytotoxic effect was observed in the methanol extract of Euphorbia hierosolymitana on HCT-116 cell line with IC50 value of 4.22 µg/mL (El-Hallouty et al, 2020). Mesas et al (2021) reported the cytotoxic effect of Euphorbia lathyris ethanol extract (IC50: 72.9±1.27 µg/mL) against HCT-115 cell line.…”
Section: Discussionmentioning
confidence: 97%
“…Screening of 346 methanol extracts of 281 native and cultivated plant species in Egypt indicated that Agave americana, A. lophantha, Furcraea selloa, Calotropis procera, Pergularia tomentosa, Asclepias sinaica, Alkanna orientalis, Khaya grandifoliola, Swietenia mahogani, Pimenta racemosa, Pinus canariensis, Verbascum sinaiticum, Solanum elaeagnifolium, S. nigrum, and Brachychiton rupestris have strong antischistosomal activity [31]. In addition, the antioxidant activity of the extract of 90 plants DOI: http://dx.doi.org/10.5772/intechopen.105193 Application of Tissue Culture Techniques to Improve the Productivity of Medicinal Secondary... was determined by 2, 2 diphenyl-1-picrylhydrazyl (DPPH) assay [32], and extracts of some plant species expressed high antioxidant and cytotoxic activities that inhibited the growth of cancer cells [33]. Leaves of A. marmelos contain several medicinal compounds including π-sitosterol, lupeol, aegelin, rutin, flavone, glycoside, marmesinine, oisopentenyl halfordiol, phenylethyl cinnamides, and marmeline [24].…”
Section: Plant Kingdom As a Source Of Medicinal Chemicalsmentioning
confidence: 99%
“…ex Boiss., Euphorbia pulcherrima Willd. ex Klotzsch, Euphorbia heterophylla L., Euphorbia helioscopia L., Euphorbia hierosolymitana Boiss., and Ricinus communis L. extracts [ 13 , 95 , 105 , 106 , 211 , 215 ]. Proapoptotic protein Bax is higher when cancer cells receive treatment with Trigothysoid N, Ebracteolatain A, and Ebracteolatain B also [ 146 , 232 ].…”
Section: Potential Anticancer Mechanism Of Action Of Euphorbiaceae Ex...mentioning
confidence: 99%